Grid power control of direct matrix converter fed three-phase induction generator - Al-Khayyat, Ali Salam; Kadhem, Human Qahtan; Hameed, Mustafa Jameel (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The direct matrix converter (DMC) and the modulation technique were presented in this paper, moreover the power of the grid is controlled. Due to its high flexibility and low computation demands, the DMC's most widely used modulation technique is space vector modulation. The double-side modulation is used in this paper instead of the single-side modulation because less harmonics at the input and output side can be obtained, however this would increase slightly the number of branch-switch-overs (BSO) for each switching period. In addition to being able to create input and output sinusoidal currents with various frequencies, it would adjust the input power factor. Along with that, the simple power control loop would regulate the grid power and then generate controlled three-phase reference signals for pulses generation accordingly. Results from the simulations show that the topology is appropriate for machine drive applications.